Tinjauan Hukum Islam tentang Promosi Dagang dengan Undian Hadiah (Studi Kasus pada Indomaret di Desa Air Jamban Kec. Mandau Kab. Bengkalis Provinsi Riau) - Ridho Muzdhalif Adha; Sofia Ridha (Lembaga Yasin AlSys, 2026)
The practice of trade promotion using prize-draw schemes is a widely employed marketing strategy in modern retail, including at Indomaret, yet this mechanism raises legal concerns when examined from the perspective of Islamic law, particularly in relation to elements of gharar, maysir, and transactional justice. This study aims to analyze the prize-draw-based trade promotion system implemented by Indomaret in Air Jamban Village, Mandau Subdistrict, Bengkalis Regency, Riau Province, and to assess its compliance with the principles of Islamic law. The research employs field research with a descriptive qualitative approach. Data were collected through observation, interviews, and documentation involving store management and consumers, and were then analyzed descriptively and analytically. The findings show that the prize-draw promotion at Indomaret in Air Jamban Village requires a minimum purchase of IDR 50,000 with certain product exclusions, while the drawing process is conducted unilaterally by Indomaret without direct consumer involvement. From the perspective of Islamic law, this practice is considered impermissible because it contains elements of uncertainty (gharar), potential deception (tadlis), and speculation that approximates gambling (maysir), while also encouraging consumptive behavior and wastefulness among consumers. The study concludes that trade promotion using a prize-draw system that is neither transparent nor fair is incompatible with the principles of Islamic commercial transactions (muamalah). The implications of this research are expected to serve as a reference for business practitioners in designing sharia-compliant promotion schemes and for Muslim consumers to adopt a more prudent and critical stance toward prize-based promotional activities.